Dark satanic mills to ivory towers: An interview with Sally R Munt, Emeritus Professor of Cultural Politics, University of Sussex, UK; and Louise Morley, Professor of Higher Education, Centre for Higher Education and Equity Research (CHEER), University of Sussex, UK. Issue 1 (2nd January 2021) - Munt, Sally R.; Morley, Louise
ABSTRACT: In this article, Sally R Munt reflects on issues of social class discrimination in higher education in an engaging conversation with Louise Morley, both from the University of Sussex.